Istisna'a Contract as a Financing Tool for Industrial Clusters - Mousa Abu Eid , Qasim (Finance and Business Economies Review, 2022)
The main objective of this study is to explore how the Istisna’ contract is used as a financing tool for industrial clusters, and how Istisna’ contracts are being used to overcome their problems to increase their effectiveness in the national economy. The study used the descriptive analytical approach to review the scientific literature of industrial clusters and the jurisprudential references to describe the Istisna’ contract and identify its role as a financing tool. As a conclusion, it was being found that Istisna’ contract is a flexible and effective financing tool that could be employed in financing and developing industrial clusters. Also it was recommended that, Islamic Banks adopt financing all components of the industrial clusters through Istisna contract.